2001
DOI: 10.1103/physrevlett.86.512
|View full text |Cite
|
Sign up to set email alerts
|

Novel Superconducting Semiconducting Superlattices: Dislocation-Induced Superconductivity?

Abstract: Novel superconducting superlattices with transition temperature in the range 2.5-6.4 K consisting only of semiconducting materials are discovered. Among them there are multilayers, including a wide-gap semiconductor as one of the components. It is shown that superconductivity is connected with the interfaces between two semiconductors containing regular grids of the misfit dislocations. The possibility of the dislocation-induced superconductivity is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 8 publications
2
26
0
Order By: Relevance
“…In one early study of dislon theory [76], we have shown that the T c is determined by this competition effect: when the quantum effect is dominant, then T c is increased, and vice versa. The computed T c shows good agreement with a number of existing experimental data; particularly, it may provide a feasible explanation of the mysterious dislocation-induced superconductivity [75,119].…”
Section: Discussionsupporting
confidence: 77%
“…In one early study of dislon theory [76], we have shown that the T c is determined by this competition effect: when the quantum effect is dominant, then T c is increased, and vice versa. The computed T c shows good agreement with a number of existing experimental data; particularly, it may provide a feasible explanation of the mysterious dislocation-induced superconductivity [75,119].…”
Section: Discussionsupporting
confidence: 77%
“…Finally, we would like to stress that the analysis of polarization-dependent EXAFS performed here to investigate the local strain at the MnSi/Si(111) interface can be widely employed, e.g., to study superconducting lattices 32,33 or heterostructures incorporating topological insulators. 34,35 This methodology provides invaluable information about the local interfacial structure, and may allow to explore its correlation with their fascinating electronic and magnetic properties.…”
Section: Discussionmentioning
confidence: 99%
“…By exploiting the linear polarization of the synchrotron radiation and by orienting the sample with the surface normal either parallel or perpendicular to the electric vector of the impinging x-rays, it is possible to probe either the out-ofplane or in-plane atomic bonds. This analysis provides direct information about strain in well-oriented thin films such as MnSi on Si(111) and could be used to investigate other systems where the local strain at the interface affects their electronic and magnetic properties as in the case of superconducting lattices 32,33 or heterostructures incorporating topological insulators. 34,35 In the following we will describe our results on differently prepared MnSi thin films as a function of film thickness.…”
Section: Introductionmentioning
confidence: 99%
“…The period of this superconducting interface nanonetwork is 5.2 nm for PbTe/PbS nanostructures. [3][4][5][6] During a comprehensive experimental investigation it was found that two-layer PbTe/PbS heterostructures can be divided nominally into 3 categories (although there is no sharp boundary between these categories). 6 The first category includes samples with semiconducting layer thicknesses d !…”
Section: Techniques For Fabricating the Samples And For Making The Trmentioning
confidence: 99%